EndoCompass project: the place of endocrinology in European research funding-an analysis of Horizon 2020 - Pandurević, Srđan; Matskevitch, Yulia; De Rijdt, Dirk (European journal of endocrinology, 2025)
Despite the substantial societal impact of prevalent endocrine diseases like obesity, diabetes, infertility, and thyroid disorders, plus over 440 rare endocrine conditions, it remains unclear whether endocrine science receives adequate research funding to address present and future health challenges. We analysed the funding for endocrine science under the EU Research Framework Programme Horizon 2020 (2014-2020) using the EU CORDIS database. Through keyword searches and European Science Vocabulary Classification Codes, we identified relevant projects and analysed total funding, distribution across endocrine areas, funding mechanisms (top-down vs bottom-up), and geographical allocation. We also conducted a preliminary analysis of the ongoing Horizon Europe (2021-2027) program. Horizon 2020 funded 331 endocrine research projects totalling €615 M, representing 3.9% of biomedical and health research funding. Nearly 70% was allocated to diabetes and obesity, with an additional 17.4% to environmental factors affecting endocrine health, predominantly through top-down funding schemes reflecting European Commission priorities. All other endocrinology areas combined received just 13.6% of endocrine funding, primarily through smaller bottom-up grants. Geographical analysis revealed significant disparities, with EU Widening Countries receiving only 4% of funding. Preliminary Horizon Europe data (€57.7 M) shows similar distribution patterns and persistent geographical inequities. The high prevalence of endocrine disorders warrants greater research funding allocation toward endocrine science. To address this funding gap, the European Society of Endocrinology and the European Society of Paediatric Endocrinology, together with partner societies and individual experts, have created the EndoCompass roadmap project-a research roadmap for better hormone health.